7x+3-4=7x+2-3

Simple and best practice solution for 7x+3-4=7x+2-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3-4=7x+2-3 equation:


Simplifying
7x + 3 + -4 = 7x + 2 + -3

Reorder the terms:
3 + -4 + 7x = 7x + 2 + -3

Combine like terms: 3 + -4 = -1
-1 + 7x = 7x + 2 + -3

Reorder the terms:
-1 + 7x = 2 + -3 + 7x

Combine like terms: 2 + -3 = -1
-1 + 7x = -1 + 7x

Add '1' to each side of the equation.
-1 + 1 + 7x = -1 + 1 + 7x

Combine like terms: -1 + 1 = 0
0 + 7x = -1 + 1 + 7x
7x = -1 + 1 + 7x

Combine like terms: -1 + 1 = 0
7x = 0 + 7x
7x = 7x

Add '-7x' to each side of the equation.
7x + -7x = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -9p=-36 | | 3m+-5+2m=7m+-24+5 | | v/2=1.77 | | 4y+9=19 | | (2n-2)=(8n+1) | | -30-x=0 | | 4x+3=11x+17 | | 2(v-6)-(-3+6v)=1-2v-2v | | u=3(4n+34)+7(n+1) | | -15x=-90 | | 2y+35=9y-7 | | n=3+3 | | 2x+42=x+42 | | 2(v-6)-(-3+6)=1-2v-2v | | 2s-10=s-2 | | 4(x^2-5x+7)-8(x^2+3x-2)= | | s-1.59=10.31 | | 2x+22=x+22 | | 800=10(15)+20y | | 1/10(x+1)= | | 3y=91+2x | | 2*3-2*x=2(3-11) | | P-18=45 | | h+1.6=5.09 | | 3(sin(X))=cos(X) | | 4-4tan^2x=0 | | 2x-3-5=8 | | D+20=2.5 | | 8lnx=7 | | 8x^2-34x-9=0 | | 3.5=z/3 | | 5m-3(-7m+4)= |

Equations solver categories